The Interplay Between the Genetic and Immune Landscapes of AML: Mechanisms and Implications for Risk Stratification and Therapy - Mendez, Lourdes M.; Posey, Ryan R.; Pandolfi, Pier Paolo (Frontiers in Oncology, 2019)
AML holds a unique place in the history of immunotherapy by virtue of being among the first malignancies in which durable remissions were achieved with “adoptive immunotherapy”, now known as allogeneic stem cell transplantation. The successful deployment of unselected adoptive cell therapy established AML as a disease responsive to immunomodulation. Classification systems for AML have been refined and expanded over the years in an effort to capture the variability of this heterogeneous disease and risk-stratify patients. Current systems increasingly incorporate information about cytogenetic alterations and genetic mutations. The advent of next generation sequencing technology has enabled the comprehensive identification of recurrent genetic mutations, many with predictive power. Recurrent genetic mutations found in AML have been intensely studied from a cell intrinsic perspective leading to the genesis of multiple, recently approved targeted therapies including IDH1/2-mutant inhibitors and FLT3-ITD/-TKD inhibitors. However, there is a paucity of data on the effects of these targeted agents on the leukemia microenvironment, including the immune system. Recently, the phenomenal success of checkpoint inhibitors and CAR-T cells has re-ignited interest in understanding the mechanisms leading to immune dysregulation and suppression in leukemia, with the objective of harnessing the power of the immune system via novel immunotherapeutics. A paradigm has emerged that places crosstalk with the immune system at the crux of any effective therapy. Ongoing research will reveal how AML genetics inform the composition of the immune microenvironment paving the way for personalized immunotherapy.